Novel Plasmodium vivax dhfr alleles from the Indonesian Archipelago and Papua New Guinea: association with pyrimethamine resistance determined by a Saccharomyces cerevisiae expression system. - Hastings, MD; Maguire, J; Bangs, M; Zimmerman, P; Reeder, J; Baird, J; Sibley, C (2005)
In plasmodia, the dihydrofolate reductase (DHFR) enzyme is the target of the pyrimethamine component of sulfadoxine-pyrimethamine (S/P). Plasmodium vivax infections are not treated intentionally with antifolates. However, outside Africa, coinfections with Plasmodium falciparum and P. vivax are common, and P. vivax infections are often exposed to S/P. Cloning of the P. vivax dhfr gene has allowed molecular comparisons of dhfr alleles from different regions. Examination of the dhfr locus from a few locations has identified a very diverse set of alleles and showed that mutant alleles of the vivax dhfr gene are prevalent in Southeast Asia where S/P has been used extensively. We have surveyed patient isolates from six locations in Indonesia and two locations in Papua New Guinea. We sequenced P. vivax dhfr alleles from 114 patient samples and identified 24 different alleles that differed from the wild type by synonymous and nonsynonymous point mutations, insertions, or deletions. Most importantly, five alleles that carried four or more nonsynonymous mutations were identified. Only one of these highly mutant alleles had been previously observed, and all carried the 57L and 117T mutations. P. vivax cannot be cultured continuously, so we used a yeast assay system to determine in vitro sensitivity to pyrimethamine for a subset of the alleles. Alleles with four nonsynonymous mutations conferred very high levels of resistance to pyrimethamine. This study expands significantly the total number of novel dhfr alleles now identified from P. vivax and provides a foundation for understanding how antifolate resistance arises and spreads in natural P. vivax populations.